Workpiece positioning sensor (wPOS): A three-degree-of-freedom relative end-effector positioning sensor for robotic manufacturing - Charrett, Thomas O. H.; Kissinger, Thomas; Tatam, Ralph P. (Elsevier, 2019)
This paper reports on the development of a new, non-contact, cost-effective and widely-applicable optical sensor for the measurement of the three degrees of translational freedom of a robotic end-effector. The workpiece positioning sensor (wPOS) tracks the relative position between the workpiece and end-effector in real-time, using laser speckle correlation for the measurement of in-plane position and Range-Resolved Interferometry for out-of-plane positioning. The sensing principles of the techniques and the development of the instrument are discussed along with example results for applications in robotic additive manufacturing for tool speed and layer height measurements.
Keywords: Displacement sensing; Process monitoring; Positioning; Tool path; Tool speed; Laser speckle; Interferometry; Range Resolved Interferometry